Criação de funcionalidades no ROODA: um foco nos aspectos socioafetivos em ambientes virtuais de aprendizagem - Akazaki, Jacqueline; Barvinski, Carla; Ferreira, Gislaine; Ribeiro, Ana Carolina Ribeiro; Longhi, Magalí; Machado, Leticia; Behar, Patricia Alejandra (Anais do Workshop de Desafios da Computação aplicada à Educação (DesafIE!), 2019)
This article presents the importance of considering the social and affective dimensions that occur in Distance Learning. Thus, it is intended to develop four functionalities for the Virtual Learning Environment of the Cooperative Learning Network (VLECLN) which are the socio-affective combination, the recommendation system, the pedagogical model and the socio-affective map. As a result, it is expected that by providing VLECLN with new features, it will be possible to create pedagogical practices more sensitive to the educational paradigm.